Pneumatic conveying of solids along a channel with different wall roughness (2014)
The present contribution describes three-dimensional Euler=Lagrange calculations of confined horizontal gas-particle flows emphasizing the importance of elementary processes, such as particle collisions with rough walls and interparticle collisions, on the predicted two-phase flow variables and pressure drop along the duct. In the chosen configuration the pneumatic conveying of spherical particles along a 6 m long horizontal channel with rectangular cross section is described from a numerical perspective. Calculations were carried out for spherical glass beads of different diameters (130 and 195 lm) with a mass loading of 1.0 (kg particles=kg gas). Additionally, different wall roughnesses were considered. In the experiments, the air volume flow rate was constant to maintain a fixed gas average velocity of 20 m=s. The numerical computations were performed by the Euler=Lagrange approach in connection with a Reynolds stress turbulence model accounting for two-way coupling and interparticle collisions. For the calculation of particle motion all relevant forces (i.e., drag, slip-shear and slip-rotational lift, and gravity), interparticle collisions and particle-rough wall collisions were considered. The agreement of the computations with the experiments of Sommerfeld and Kussin (2004) was found to be satisfactory for pressure drop and mean and fluctuating velocities of both phases as well as for the normalized particle mass flux